Interpreting Translation: Studies on the LXX and Ezekiel in Honour of Johan Lust. Edited by F. García Martínez and M. Vervenne, with the collaboration of B. Doyle - Salvesen, A. G. (The journal of theological studies, 2008)
The general pressure of work on scholars today and the increase in the number of invitations to write for Festschriften often mean that such a volume can be a collection of unrelated if not uninteresting titbits. In this case, however, most of the studies relate to an aspect of Lust's own work, such as the books of Jeremiah and Ezekiel in both Hebrew and Greek, and more generally the Greek versions of the Bible. Some of the studies are significant contributions to the field. However, the volume presents the essays in alphabetical order of authors' names, which tends to obscure the more obvious thematic groupings., Of the authors focusing on the book of Jeremiah, Anneli Aejmelaeus looks at the curious appellation ‘Nebuchadnezzar my servant’ in MT of Jer.